A Naphthalenic Derivative ND-1 Inhibits Thrombus Formation by Interfering the Binding of Fibrinogen to Integrin αIIbβ3. (20th December 2016) - Ding, Xue; Liu, Tong-dan; Xie, Zhou-ling; Zhao, Qi; Cao, Yuan; Liu, Xiao-dong; Wang, Cai-hui; Gamariel, Rwibasira Rudinga; Ming, Xin; Li, Zhi-yu; Kong, Yi
Abstract : Integrin α IIb β 3 plays a crucial role in the process of platelet aggregation. Three integrin α IIb β 3 antagonists (abciximab, eptifibatide, and tirofiban) have been approved by FDA for clinical use. Unfortunately, they all showed severe side effects such as thrombocytopenia and bleeding risk. Thus, researches on the development of more effective and safer antiplatelet agents are needed. In this manuscript we reported a novel naphthalenic derivative compound ND-1 with potent antithrombotic effect and lower bleeding risk. ND-1 inhibited ADP-, collagen-, thrombin-, and U46619-induced platelet aggregation with IC50 values of 1.29, 14.46, 12.84, and 40.24 μ M, respectively. Mechanism studies indicated that ND-1 inhibited the binding of fibrinogen to integrin α IIb β 3 in a dose-dependent manner with an IC50 value of 3.12 μ M. ND-1 inhibited P-selectin expression induced by ADP, collagen, thrombin, and U46619 on the surface of platelets. Additionally, this compound reduced platelets spreading to the immobilized fibrinogen. In vivo, ND-1 potently decreased thrombus formation in an arteriovenous shunt thrombosis model in rats and slightly prolonged bleeding time in a tail cutting model in mice. Taken together, our results reveal that ND-1 is a novel antagonist of α IIb β 3 with strong antithrombotic effect and lower bleeding risk.